Polyphenol-rich Spondias mombin leaf extract abates cerebral ischemia/reperfusion-induced disturbed glutamate-ammonia metabolism and multiorgan toxicity in rats. (2nd January 2023) - Ojo, Olubukola Benedicta; Olajide, Abigail Oladunni; Olagunju, Grace Boluwatife; Olowu, Comfort; Josiah, Sunday Solomon; Amoo, Zainab Abiola; Olaleye, Mary Tolulope; Akinmoladun, Afolabi Clement
ABSTRACT: Introduction: This study investigated the protective properties of Spondias mombin leaf extract (SML), in cerebral ischemia/reperfusion (I/R) mediated toxicity in the brain, liver, and kidney of male Wistar rats. Materials and methods: Animals were subjected to 30 min of bilateral common carotid artery occlusion followed by 24 h of reperfusion (BCCAO/R). The animals were divided into sham, I/R, and I/R treated with SML (25, 50 and 100 mg/kg) or quercetin (20 mg/kg) groups. Animals were sacrificed after 24 h of reperfusion and markers of organ toxicity (urea creatinine, glutamine synthetase (GS), glutaminase (GA), aspartate aminotransferase (AST), alanine aminotransferase (ALT), acetylcholinesterase (AChE)) were measured in the brain regions (cortex, striatum, and hippocampus), liver, and kidney. Results and discussion: BCCAO/R significantly ( p  < 0.0001) inhibited the glutamate-glutamine cycle and mediated toxicity in the cerebral cortex, striatum, hippocampus, liver, and kidney of rats. Post-treatment with SML significantly ( p  < 0.0001) reversed glutamate-glutamine cycle inhibition and ameliorated cerebrohepatorenal toxicity in ischemic rats. Conclusion: Cerebral I/R significantly mediated cerebral, hepatic, and renal toxicity through the inhibition of glutamate-ammonia detoxification in rats, and SML protected against this post-ischemic glutamate-ammonia mediated multiorgan toxicity.